Crosstalk between p53 and TGF-β Signalling. (28th March 2012) - Elston, Rebecca; Inman, Gareth J.
Abstract : Wild-type p53 and TGF- β are key tumour suppressors which regulate an array of cellular responses. TGF- β signals in part via the Smad signal transduction pathway. Wild-type p53 and Smads physically interact and coordinately induce transcription of a number of key tumour suppressive genes. Conversely mutant p53 generally subverts tumour suppressive TGF- β responses, diminishing transcriptional activation of key TGF- β target genes. Mutant p53 can also interact with Smads and this enables complex formation with the p53 family member p63 and blocks p63-mediated activation of metastasis suppressing genes to promote tumour progression. p53 and Smad function may also overlap during miRNA biogenesis as they can interact with the same components of the Drosha miRNA processing complex to promote maturation of specific subsets of miRNAs. This paper investigates the crosstalk between p53 and TGF- β signalling and the potential roles this plays in cancer biology.